2014
DOI: 10.5267/j.msl.2014.8.006
|View full text |Cite
|
Sign up to set email alerts
|

A study on ranking the effects of transformational leadership style on organizational agility and mediating role of organizational creativity

Abstract: The purpose of this study was to investigate the effects of the components of transformational leadership style on organizational agility and mediating role of organizational creativity in Ilam Gas Refinery located in province of Ilam, Iran. The method of the present study was descriptive and correlational-structural equation modeling. The population of this research included all 400 workers of Ilam gas refinery and the study chose a sample of196 employees. The questionnaire was standardized using Cronbach's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Through leadership the employees can be directed to the achievement of OA. The results of previous empirical studies (Aurélio de Oliveira et al, 2012;Karimi et al, 2016;Raeisi & Amirnejad, 2017;Veiseh et al, 2014) indicated that leadership positively influenced the OA. It can be interpreted that the improvement of EL will affect the improvement of OA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Through leadership the employees can be directed to the achievement of OA. The results of previous empirical studies (Aurélio de Oliveira et al, 2012;Karimi et al, 2016;Raeisi & Amirnejad, 2017;Veiseh et al, 2014) indicated that leadership positively influenced the OA. It can be interpreted that the improvement of EL will affect the improvement of OA.…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies have highlighted the importance of leadership in building OA. The results of previous studies show a positive influence of leadership style on OA (Hosseini et al, 2013;Karimi et al, 2016;Raeisi & Amirnejad, 2017;Veiseh et al, 2014).…”
Section: Hypothesis Developmentmentioning
confidence: 86%
“…Agile leaders not only have the ability to function in complex situations, but they also prepare the employees to tackle unpredictable challenges in an appropriate manner. Leaders empower employees to make decisions under unpredictable conditions using their imagination and experience leading them in the process of learning (Veiseh and Eghbali, 2014; Voolaid and Ehrlich, 2017). A leader plays a crucial role in creating organizational purpose, supporting innovation and entrepreneurial activities, building teams, deciphering the behavioral pattern of employees, transforming their capabilities to match the business needs and ensuring strategies, policies and structure support the core values of the organization (Crocitto and Youssef, 2003; Giesecke and McNeil, 2004; Bunton, 2017; Strode et al , 2009; Ananthram and Nankervis, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies investigate specific leadership styles. For example, Veiseh et al [76] showed that agile leaders are more transformational. Garcia et al [22] found that the effectiveness of different leadership styles are independent of the software development process (e.g.…”
Section: Research On Leadership In Software Engineeringmentioning
confidence: 99%